Are drone strikes effective in Afghanistan and Pakistan? On the dynamics of violence between the United States and the Taliban - David A. Jaeger; Zahra Siddique (Institute for the Study of Labor (IZA), 2011)
Strikes by unmanned aerial vehicles, or drones, have been the primary weapon used by the United States to combat the Taliban and Al-Qaeda in Afghanistan and Pakistan. This paper examines the dynamics of violence involving drone strikes and the Taliban/Al-Qaeda in Afghanistan and Pakistan from January 2007 to December 2010. We find that drone strikes do not have any significant impact on terrorist violence in Afghanistan but that drone strikes do have a significant impact on Taliban/Al-Qaeda violence in Pakistan. We find that our results are robust to examining different time periods and lag structures. We also examine the impact of successful and unsuccessful drone strikes (which did or did not succeed in targeted killing of a militant leader) on terrorist attacks by the Taliban. We find strong negative impacts of unsuccessful drone strikes on Taliban violence in Pakistan, showing the deterrent effects are quite strong, while the incapacitation effects appear to be weak or non-existent.
urn:nbn:de:101:1-201203016420
Keywords: C32; D74; 330; time series models; conflict; Krieg; USA; Politische Gewalt; Afghanistan; Pakistan